# Answer on Trigonometry Question for klaudia

Question #12901

1. Use Demoivre Theorem. Express result in standard form.

(1+i)^7

2.verify:

a)cosx(tang^2x+1)=secx

b)(sinx) / (1-cosx) = (1+cosx) / (sinx)

3. Solve:

a)2sin^2x-sinx-1=0

b)tang^2x-1=0

c)cosx+sqrt(3) = -cosx

(1+i)^7

2.verify:

a)cosx(tang^2x+1)=secx

b)(sinx) / (1-cosx) = (1+cosx) / (sinx)

3. Solve:

a)2sin^2x-sinx-1=0

b)tang^2x-1=0

c)cosx+sqrt(3) = -cosx

Expert's answer

Unfortunately, your question requires a lot of work and cannot be done for free.

Submit it with all requirements as an assignment to our control panel and we'll assist you.

Submit it with all requirements as an assignment to our control panel and we'll assist you.

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment